2007
DOI: 10.1124/mi.7.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Damage in Cancer Chemotherapy: Oxidative Stress in Nontargeted Tissues

Abstract: Injury to nontargeted tissues in chemotherapy often complicates cancer treatment by limiting therapeutic dosages of anticancer drugs and by impairing the quality of life of patients during and after treatment. Oxidative stress, directly or indirectly caused by chemotherapeutics as exemplified by doxorubicin, is one of the underlying mechanisms of the toxicity of anticancer drugs in noncancerous tissues, including the heart and brain. A comprehensive understanding of the mechanisms of oxidative injury to normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
264
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 341 publications
(271 citation statements)
references
References 72 publications
4
264
0
3
Order By: Relevance
“…Free radical-mediated oxidative stress has been proposed as a potential mechanism underlying DOX toxicity in the brain [4]. In accordance, we observed that DOX treatment increases TBARS levels (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Free radical-mediated oxidative stress has been proposed as a potential mechanism underlying DOX toxicity in the brain [4]. In accordance, we observed that DOX treatment increases TBARS levels (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…However, much less is known about the effects of DOX treatment in the brain. Although previous studies indicate that cancer patients under DOX therapy present signs of cognitive decline [4], the mechanisms underlying these cognitive alterations remain unknown.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations